CHARGE‐like presentation, craniosynostosis and mild Mowat–Wilson Syndrome diagnosed by recognition of the distinctive facial gestalt in a cohort of 28 new cases. Issue 10 (14th August 2014) - Wenger, Tara L.; Harr, Margaret; Ricciardi, Stefania; Bhoj, Elizabeth; Santani, Avni; Adam, Margaret P.; Barnett, Sarah S.; Ganetzky, Rebecca; McDonald‐McGinn, Donna M.; Battaglia, Domenica; Bigoni, Stefania; Selicorni, Angelo; et al.
Abstract : Mowat–Wilson syndrome (MWS) is characterized by moderate to severe intellectual disability and distinctive facial features in association with variable structural congenital anomalies/clinical features including congenital heart disease, Hirschsprung disease, hypospadias, agenesis of the corpus callosum, short stature, epilepsy, and microcephaly. Less common clinical features include ocular anomalies, craniosynostosis, mild intellectual disability, and choanal atresia. These cases may be more difficult to diagnose. In this report, we add 28 MWS patients with molecular confirmation of ZEB2 mutation, including seven with an uncommon presenting feature. Among the "unusual" patients, two patients had clinical features of charge syndrome including choanal atresia, coloboma, cardiac defects, genitourinary anomaly (1/2), and severe intellectual disability; two patients had craniosynostosis; and three patients had mild intellectual disability. Sixteen patients have previously‐unreported mutations in ZEB2 . Genotype‐phenotype correlations were suggested in those with mild intellectual disability (two had a novel missense mutation in ZEB2, one with novel splice site mutation). This report increases the number of reported patients with MWS with unusual features, and is the first report of MWS in children previously thought to have CHARGE syndrome. These patients highlight the importance of facial gestalt in the accurate identification of MWS when less common features are present. © 2014 Wiley Periodicals, Inc.